Enhanced gasification effect from discharges and the formation of centimeter-scale plasma during microwave combustion of coke. (15th January 2023) - Su, Yanlin; Zhou, Wei; Li, Junfeng; Gao, Jihui; Wang, Pengxiang; Zhao, Guangbo; Qin, Yukun
Graphical abstract: Highlights: Conditions necessary for the generation of stable centimeter-scale microwave plasma were discussed. An enhanced gasification was observed during microwave combustion of coke. CO production and microwave discharge intensity showed a clear correlation. Discharges and flame combustion boost each other simultaneously. Abstract: Microwave technology has been demonstrated as a promising candidate for utilizing fossil fuel in a carbon-efficient manner to ensure energy supply security during the transition to the future green energy economy. Microwave plasma enhancement on gas fuel combustion has been demonstrated, which is attributed to the production of reactive radicals and fuel cracking. However, for solid fuels with low volatilities and ignition and combustion efficiency problems, such as coke; it is still unknown whether the discharge plasma can assist in destroying its aromatic structure, thereby producing extra combustible gases. This process may be a common concern associated with various gas–solid heterogeneous reactions using coal as a reactant. In this study, a centimeter-sized plasma was generated during the combustion of coke under microwave radiation, which significantly promoted the flame burning. Two main factors accounting for the formation of centimeter-scale plasma are discussed: the carbonization temperature and particle size of coke. Additionally, the correlation between CO production and microwave discharge was also examined. Finally, the synergistic promotion mechanism of flame combustion and microwave discharge is proposed. This paper provides new insights into the microwave enhancement mechanism in gas–solid heterogeneous reactions.